Effects in Conventional Nonlinear Static Analysis: Evaluation of Control Node Position. (February 2018) - Uva, Giuseppina; Porco, Francesco; Fiore, Andrea; Ruggieri, Sergio
Abstract: The nonlinear methods of analysis are the most indicated ones to carry out the vulnerability assessment of existing Reinforced Concrete (RC) buildings. Notwithstanding nonlinear approaches strongly depends by the knowledge level of building, they allow to obtain the effective response of structure, due to the combined effect of both dead and seismic loads. However, these methods are based on conventional choices that, in some cases, can modify the results that are affected of a significant uncertainty level. Concerning to nonlinear static method, one of the fixed point at the base of analysis is the choice of control node (point in which the displacement of the structure under horizontal load is monitored) coincident with the centre of mass of last storey of building. This assumption is significant when, in order to verify the structural capacity with N2 method, an equivalent Single Degree of Freedom (SDoF) system is considered, neglecting the real variability of centre of mass position, provided by the accidental loads. In the present work, it will be shown as the structural capacity (in terms of displacement at Life Safety Limit State) with reference to several cases of existing RC buildings can be strongly affected by the choice of the control node position. In particular, 28 existing RC buildings were analysed. These are part of a large sample of example cases made according to geometric and mechanics features of real existing buildings. The peculiarity of the "ideal" buildings consist in an irregular in-plan shape but with dynamic properties such as to allow the applicability of pushover analysis and, consecutively, the application of N2 method. In order to optimize the procedure of choice of control node, a parametric formulation is proposed, depending by dimensionless geometric features, able to estimate the variability of capacity curve at variation of control node position. This approach is mainly finalized to expeditious estimate of structural behavior for RC buildings of urban aggregate and it is a base for formulation ad hoc to evaluate the structural response of dynamic irregular buildings.